Vivências de ser cuidador familiar de idosos dependentes no ambiente domiciliar - Alcimar Marcelo do Couto; Edna Aparecida Barbosa de Castro; Célia Pereira Caldas (Universidade Federal do Ceará, 2016)
Objective: to understand the experience of caring for dependent elderly in the home environment, from the perspective of family caregivers that present burden and emotional distress. Methods: this is a qualitative research with a contribution in the Theory Grounded in Data. There were home visits for observation and semistructured interviews with nine relatives of dependent elderly in self-care. Results: with the coding and analysis of empirical data, one can understand the daily cares in the care relationship with their elderly dependent relatives. The consolidated experiences underlie on positive experiences, such as solidarity by the established interaction and the maintenance of self-esteem, and negative as changes in daily routine and health, with stress identification related to the caregiver role. Conclusion: in the understanding of the family, their experiences as a caregiver in the home context varied between positive and negative aspects, which respectively minimize and maximize the feeling of burden and emotional distress.